Role of healthcare databases and registries for surveillance of orphan drugs in the real-world setting: the Italian case study. Issue 6 (3rd June 2019) - Crisafulli, Salvatore; Sultana, Janet; Ingrasciotta, Ylenia; Addis, Antonio; Cananzi, Pasquale; Cavagna, Lorenzo; Conter, Valentino; D'Angelo, Gabriella; Ferrajolo, Carmen; Mantovani, Lorenzo; Pastorello, Maurizio; Scondotto, Salvatore; et al.
ABSTRACT: Introduction : Orphan drugs are medicines intended to treat, prevent, or diagnose a rare and serious condition. The collection of pre-marketing safety and efficacy data for orphan drugs is very challenging for several reasons related to the rarity of the diseases. This highlights the need for robust post-marketing evidence generation. Real-world data sources, such as claims databases, electronic healthcare records, and disease and drug registers, have an important role in studying orphan drugs. The availability and usefulness of such resources vary from country to country. Areas covered : A detailed description of the available real-world data sources and their contribution to generating post-marketing evidence on orphan drug benefit-risk profile in Italy is provided. Expert opinion : Despite their considerable potential for rare disease research, the available Italian data sources are currently under-used and require further harmonization of data collection. The establishment of large structured and integrated nationwide data sources, tailored to respond to both research as well as regulatory requirements, is necessary to provide clinically useful information on orphan drugs as well. Such data sources should also be more accessible at the loco-regional, national and international level.